Stay on trails: Detrimental effects of recreational activities on soil compaction and infiltration - Saputra, Danny Dwi; Putra, Aditya Nugraha; Sari, Rika Ratna; Ishaq, Rizki Maulana; Hadiwijoyo, Erekso; Hadi, Maruf; Suprayogo, Didik (Journal of Degraded and Mining Lands Management, 2024)
Bromo Tengger Semeru National Park (BTS-NP) in East Java, Indonesia showcases a breathtaking volcanic landscape and cultural allure, drawing hundreds of thousands of domestic and international visitors. Recreational activities involving human and animal trampling and motorized-vehicle traffic caused soil disturbance along their networks of paths, trails, or roads, potentially having a detrimental long-term effect on the tourism industry and environmental services provided by the national parks. However, the extent of the impact of these disturbances on soil properties remains unclear.  This study assessed the impact of different disturbance intensities, consisting of undisturbed locations as a control (zone 1), low to medium- (zone 2), and high- (zone 3) disturbance intensities on five different BTS-NP tourism hotspots, including Entrance Wonokitri (EW), Whispering Sand (WS), Parking Temple (PT), Teletubbies Hill (TH), and Entrance Bromo Stairs (EB), on soil properties, including soil compaction represented by soil penetration resistance, and soil infiltration. This study revealed that the higher severity impact of recreational activities on soil compaction was parallel with higher disturbance intensity, particularly in EW and TH. In these particular locations, higher soil compaction is significantly linked to lower soil infiltration, thus needing extra attention and protection. Meanwhile, in WS, PT, and EB, soil infiltration was more controlled by the establishment of a cemented topsoil layer consisting of mixed sand, sulfur, and water. Better management strategies, such as the use of proper trails and road infrastructures, particularly on EW and TH, might be relevant to minimize the impact of recreational activities on these ecologically, economically, and culturally important areas.